PENDIDIKAN GRATIS BERBASIS 5 PILAR MANAJEMEN MUTU TERPADU - Rusman Roni (Publikasi Penelitian Terapan dan Kebijakan, 2020)
The article reports five important stages to be put into account, they are:1) educational input, 2)process, , 3) product.4) committment 5)organization. The problem is as follows: How are 1) educational input, 2)process, , 3) product.4) committment 5)organization managed at South-Sumatera?. Method utilized in this study is descriptive technique and by using snowball technique. This is a process of gathering data taken from news paper especially Sindo. This finding indicates that the cumpulsoryand free education driven from APBN(National budget planning) for primary school to yunior high school.whereas senior high school is funded by APBD(Regional budget planning). Another finding indicates that 20 private school ignored bos (operational system of education. With regard to the problems, there are four main problems, they are:1) general and particular problems, 2) budgeting problem 3) political problems, organization problems, . In relation to solution and suggestions, several ways to cope with those problems. They are: commitment, raising the fund for the students and other components of education such facilities, teachers training etc